2020
DOI: 10.1002/adom.202000201
|View full text |Cite
|
Sign up to set email alerts
|

Enabling and Controlling Negative Photoconductance of FePS3 Nanosheets by Hot Carrier Trapping

Abstract: to the photon-assisted oxygen desorption from the nanostructure surface, resulting in a decrease of hole concentration. [2] Also, in the case of n-type InAs nanowires, the hot carrier trapping process at the surface gives the reduction of photoexcited charge carriers. [3] Therefore, additional electronic states are always required to compensate photoexcited charge carriers for accessing NPC situation. Nanostructured materials with plenteous surface sites can potentially generate a high density of localized ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…[ 27 ] Monotonic and predictable absorption edge shift within the temperature range covered by present state‐of‐the‐art thermoelectric cells (200–250 K) [ 46 ] is relevant for extending the usefulness of FePS 3 as the active material for low‐noise cooled photodetectors covering a broad spectral range from near‐infrared up to ultraviolet. [ 27–29 ] The characteristic region of anomalous temperature dependence coincides with a transition from the paramagnetic (PM) to the antiferromagnetic (AFM) phase of FePS 3 (Néel temperature). [ 47–50 ] The same behavior has been observed on a few samples of the synthesized material and during multiple heating/cooling cycles on the same sample, proving good reversibility of the phase transition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 27 ] Monotonic and predictable absorption edge shift within the temperature range covered by present state‐of‐the‐art thermoelectric cells (200–250 K) [ 46 ] is relevant for extending the usefulness of FePS 3 as the active material for low‐noise cooled photodetectors covering a broad spectral range from near‐infrared up to ultraviolet. [ 27–29 ] The characteristic region of anomalous temperature dependence coincides with a transition from the paramagnetic (PM) to the antiferromagnetic (AFM) phase of FePS 3 (Néel temperature). [ 47–50 ] The same behavior has been observed on a few samples of the synthesized material and during multiple heating/cooling cycles on the same sample, proving good reversibility of the phase transition.…”
Section: Resultsmentioning
confidence: 99%
“…Iron phosphorus trisulfide, FePS 3 , attracts a lot of attention in that term. It has been shown to exhibit extraordinary photoconductive performance [27][28][29] arising from high carrier mobility and broadband optical absorption above the bandgap (1.2-1.5 eV depending on the experimental technique [23,24,29] ) close to the optimal for solar cells as determined by the Shockley-Queisser limit. Negative photoconductivity [28] has also been observed in thin layers of FePS 3 for illumination with photons of energy around trap states within the conduction band, switchable in sign and magnitude by applying a gate voltage, [27] giving another parameter to control the device performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27]58,59] The study, which reported linear I-Vs for FePS 3 devices, was limited to the lower voltage regimes. [60] The exact nature of the non-linearity at high bias voltage is still an open question. While some studies attributed it to the formation of the Schottky barriers at the junction between the channel and the metal contacts, [25][26][27]58] the I-V characteristics of our devices plotted in semi-logarithmic scale (se(c)) suggest deviation from the conventional Schottky barrier thermionic model.…”
Section: Resultsmentioning
confidence: 99%
“…To further understand this unique photoresponse, we propose a comprehensive analytical model which, unlike any previously reported models, [ 25,26,64 ] accounts for both positive and negative photoresponse. For a nonequilibrium system, we summarize a set of equations and consider the frequency‐dependent rate equations governing the densities of photogenerated hot electrons and holes ( n hot and p hot ), trapped holes ( p trp ), and relaxed electrons and holes at conduction and valence band edges (Δ n and Δ p ) in this model.…”
Section: Figurementioning
confidence: 99%